2023
DOI: 10.1038/s41467-023-38396-7
|View full text |Cite
|
Sign up to set email alerts
|

A sensory memory processing system with multi-wavelength synaptic-polychromatic light emission for multi-modal information recognition

Abstract: Realizing multi-modal information recognition tasks which can process external information efficiently and comprehensively is an urgent requirement in the field of artificial intelligence. However, it remains a challenge to achieve simple structure and high-performance multi-modal recognition demonstrations owing to the complex execution module and separation of memory processing based on the traditional complementary metal oxide semiconductor (CMOS) architecture. Here, we propose an efficient sensory memory p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Furthermore, once the hardware network is constructed, changing weights becomes extremely costly as the weights are typically expressed using transmittance, which is fixed and unchangeable. Furthermore, despite some efforts have proposed artificial luminescent synapses, these devices only employed one output (optical or electrical signal) for transmission in the neural network, failing to propose effective strategies to leverage the dual-output potential of devices and achieve powerful networks 13 , 34 , 43 . Hence, a strategy utilizing dual-output characteristics of N-LEM to construct cross-layer transmission block (ClBlock) was proposed to achieve an ultra-deep photoelectric neural network (UPENN) and ultra-deep super-resolution reconstruction neural network (USRNN) with transfer learning ability (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, once the hardware network is constructed, changing weights becomes extremely costly as the weights are typically expressed using transmittance, which is fixed and unchangeable. Furthermore, despite some efforts have proposed artificial luminescent synapses, these devices only employed one output (optical or electrical signal) for transmission in the neural network, failing to propose effective strategies to leverage the dual-output potential of devices and achieve powerful networks 13 , 34 , 43 . Hence, a strategy utilizing dual-output characteristics of N-LEM to construct cross-layer transmission block (ClBlock) was proposed to achieve an ultra-deep photoelectric neural network (UPENN) and ultra-deep super-resolution reconstruction neural network (USRNN) with transfer learning ability (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that the surface potential increase and then decrease after irradiation compared to dark, and the degree of decay increases with increasing light intensity. Given that the decrease (increase) of the film surface potential is correlated with the increase (decrease) of the film electron concentration, [17] from a field effects perspective, the effect of the V GS on the channel modulation is diminished by some factor when the device is subject to irradiation.…”
Section: Working Mechanism Of Mp-onhmentioning
confidence: 99%
“…Modulation of pulse frequency is also important for neuronal functioning . As shown in Figure a, under DUV light stimulation, when the light pulse frequency was increased from 0.5 to 10 Hz, the EPSC was gradually increased from 8.77 to 11.09 nA, and good regulation was achieved.…”
mentioning
confidence: 99%